Participatory culture in a networked era : a conversation on youth, learning, commerce, and politics - Jenkins, Henry, 1958-; Ito, Mizuko; boyd, danah, 1977- (Cambridge, UK ; Malden, MA, USA : Polity Press, 2016)
In the last two decades, both the conception and the practice of participatory culture have been transformed by the new affordances enabled by digital, networked, and mobile technologies. This exciting new book explores that transformation by bringing together three leading figures in conversation. Jenkins, Ito and boyd examine the ways in which our personal and professional lives are shaped by experiences interacting with and around emerging media. Stressing the social and cultural contexts of participation, the authors describe the process of diversification and mainstreaming that has transformed participatory culture. They advocate a move beyond individualized personal expression and argue for an ethos of "doing it together" in addition to "doing it yourself." Participatory Culture in a Networked Era will interest students and scholars of digital media and their impact on society and will engage readers in a broader dialogue and conversation about their own participatory practices in this digital age.
Defining participatory culture -- Youth culture, youth practices -- Gaps and genres in participation -- Learning and literacy -- Commercial culture -- Democracy, civic engagement, and activism -- Reimagining participatory culture.
Includes bibliographical references (pages 188-201) and index.
Keywords: Internet and youth; Online social networks; Technology and youth; Youth -- Social life and customs; Youth -- Political activity